2021
DOI: 10.1177/08883254211018770
|View full text |Cite
|
Sign up to set email alerts
|

Bringing the Virus Back Home: Media Representations of Ukrainian Labour Migrants in a Time of Pandemic

Abstract: In a globalized world where mobility and movement is at its essence, the movement of viruses paradoxically causes a preoccupation with boundaries, containment, and control over borders, and thus keeping the “dangerous” outside separated from the “safe” inside. Through a qualitative thematic and frame analysis of news articles published on 12 Ukrainian news sites, I found that Ukrainian labour migrants conceptually constitute a challenge to such a clear-cut spatial organization in a time of a pandemic. Labour m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…En este contexto, se representó a las personas migrantes como amenaza, relacionándolas con problemas económicos, de salud pública y de inseguridad (Méndez-Fierro y Reyes-Piñuelas, 2022). Además, junto con las representaciones de la migración como portadora de un peligro, convivió aquella de éstas como recurso económico y como víctima (Tymczuk, 2022). Así, como sucede en otros contextos de crisis (Chouliaraki y Stolic, 2017), se dejaba entrever la emergencia de significados disímiles y contrapuestos.…”
Section: Representación Mediática De La Migración Y En El Contexto De...unclassified
See 2 more Smart Citations
“…En este contexto, se representó a las personas migrantes como amenaza, relacionándolas con problemas económicos, de salud pública y de inseguridad (Méndez-Fierro y Reyes-Piñuelas, 2022). Además, junto con las representaciones de la migración como portadora de un peligro, convivió aquella de éstas como recurso económico y como víctima (Tymczuk, 2022). Así, como sucede en otros contextos de crisis (Chouliaraki y Stolic, 2017), se dejaba entrever la emergencia de significados disímiles y contrapuestos.…”
Section: Representación Mediática De La Migración Y En El Contexto De...unclassified
“…En relación con esto, y analizando la representación de migrantes laborales ucranianos en medios ucranianos, Tymczuk (2022) hace una interesante propuesta señalando que, durante la pandemia, migrantes laborales que retornaban a sus países no se les excluía de la comunidad imaginada. No obstante, se construiría otro tipo de otredad en relación con una supuesta "inmunidad imaginada" (Tymczuk, 2022). Estas construcciones evidencian que movilidad e inmovilidad, migrantes internacionales y connacionales, pueden situarse de diferentes maneras en discursos marcados por la otredad.…”
Section: Representación Mediática De La Migración Y En El Contexto De...unclassified
See 1 more Smart Citation
“…These difficulties were coupled with the practices deployed in the third countries, as in Ukraine, where the authorities restricted cross-border mobility for short periods in spring 2020. Ultimately, despite a declaration on the closure of all border crossings, the Ukrainian authorities did not opt for strict solutions in this regard (Tymczuk, 2021;Wolska, 2020). Despite all restrictions on border crossing, farmworkers from Ukraine could count on exceptional treatment based on the regulations implemented in Poland, but also in other countries welcoming farmworkers from Ukraine amidst pandemic times (e.g.…”
Section: Overcoming Difficulties In Crossing the Border Of The Europe...mentioning
confidence: 99%
“…The employers with whom we were in contact did not perceive the migrant population as a threat, nor as agents spreading the virus. However, the press portrayed Ukrainian labour migrants differently, and framed them as a major epidemiological threat to the local communities in Ukraine (Tymczuk, 2021). Similarly, during an outbreak of COVID-19 on farm in north-east Poland, a one of the biggest regional daily papers reported that seasonal workers had circumvented the restrictions and entered Poland via Czechia and Slovakia, thus escaping the obligatory quarantine for arrivals from Ukraine, indirectly pointing to migrant workers as disease spreaders (Kurs, 2020).…”
Section: Let's Stop Talking About This Stupid Pandemic All the Time! ...mentioning
confidence: 99%